Sharjah Biennial 16: Sonic Inheritances (Sharjah Art Foundation; Bergen Assembly, Norway, 2025)
Artist project. Texts: Singing Wells, abubilla Arts Foundation, Tabu Osusa, Helena Carone Wheatley, Iona Gaskell.
Arabic
Keywords: Biennial guidebook; N4390-5098 Visual Arts- Exhibitions; Palestine -- Gaza